Impact of psychological contract breach on firm’s innovative performance: A moderated mediation model - Zhang, Lizhe (Frontiers in Psychology, 2022)
Organizations are seeking ways to be more competitive in the market. Globalization also paves the way for additional challenges for firms to compete in today's knowledge-based economy and competitive corporate settings. The psychological contract breach of employees could be a possible reason to slow down the firm's innovative performance. Based on the social exchange theory, the present study assumes that a psychological contract breach negatively affects a firm’s innovative performance. The present study also assessed the mediating role of knowledge hiding and moral disengagement in the relationship between psychological contract breach and a firm’s innovative performance. This study also attempts to check the moderating role of perceived supervisor support in the relationship between psychological contract breach and knowledge hiding and between psychological contract breach and moral disengagement. For empirical investigation, the present study collected the data from 303 employees of various textile organizations in china through a structured questionnaire method using a convenient sampling technique. The present study applied partial least square structural equation modeling for empirical analyses using Smart PLS software. The present study revealed that a psychological contract breach does not directly influence a firm’s innovative performance. However, the results confirmed that knowledge hiding negatively mediates the relationship between psychological contract breach and a firm’s innovative performance. On the other hand, results also confirmed that moral disengagement negatively mediates the relationship between psychological contract breach and a firm’s innovative performance. The finding also acknowledged that the perceived supervisor support does not moderate the relationship between psychological contract breach and knowledge hiding. Additionally, the findings confirmed that perceived supervisor support positively moderates the relationship between psychological contract breach and moral disengagement. The present study offers important practical, theoretical, and managerial implications.